Criminal Liability of Fintech Company for Spreading Personal Data - Rosada, Imam (Pemuliaan Hukum, 2023)
Globally, information technology has altered human behavior and way of life. The world has no borders now that information technology has advanced. Information technology has now evolved into a double-edged sword because, in addition to advancing human civilization and welfare, it also provides effective means for criminals to commit crimes, such as the dissemination of personal data by fintech (pinjol). As a result, laws that punish online lenders (pinjol) who spread personal data are now necessary. The purpose of this study is to identify criminal liability for the fintech (pinjol) conduct of disclosing personal information and to identify law enforcement. An strategy that is normatively legal is used in this study. In addition, this study employs primary law, secondary legal materials, and tertiary legal materials in a descriptive-analytical manner. The descriptive-analytical research methodology utilized in this study describes the applicable laws and rules connected to legal theories and the practice of enforcing positive legislation. According to the criminal liability view of criminal responsibility considered from the repercussions it can do harm to others, both physically and mentally, fintech (pinjol) is responsible for the act of disclosing personal data. It is reasonable that the act of disseminating personal data might be subject to the threat of penalty as defined in the ITE Constitution and the Dissemination of Personal Data Law since those who commit crimes are considered to have done so intentionally (Opzet) with a goal. Law enforcement's ability to prevent the dissemination of personal data is currently limited and challenging due to the difficulty of enforcing the legality standard. As a result, the ratification of the Dissemination of Personal Data Regulation was a breath of fresh air for law enforcement.Teknologi informasi telah mengubah perilaku dan pola hidup masyarakat secara global. Perkembangan teknologi informasi telah menyebabkan dunia menjadi tanpa batas (borderless). Teknologi informasi saat ini telah menjadi pedang bermata dua, karena selain memberikan kontribusi bagi peningkatan kesejahteraan, kemajuan dalam peradaban manusia, sekaligus menjadi sarana efektif untuk para pelaku melakukan tindak pidana, seperti Penyebaran data pribadi yang dilakukan oleh perusahaan fintech (pinjol), sehingga perlunya penegakan hukum terhadap pelaku pinjaman online (pinjol) yang menyebarkan data pribadi. Penelitian ini bertujuan Untuk mengetahui tanggung jawab pidana atas tindakan penyebaran data pribadi yang dilakukan oleh perusahaan fintech (pinjol) serta Untuk mengetahui penegakan hukumnya. Penelitian ini menggunakan metode pendekatan yuridis normatif, Penelitian ini juga dilakukan dengan cara deskriptif analitis yaitu menggunakan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Metode yang digunakan dalam penelitian ini adalah bersifat deskriptif analitis, yaitu menggambarkan peraturan perundang-undangan yang berlaku dikaitkan dengan teori-teori hukum dan praktek pelaksanaan hukum positif. Tanggung jawab pidana atas tindakan penyebaran data pribadi yang dilakukan oleh perusahaan fintech (Pinjol) dalam pandangan pertanggungjawaban pidana dilihat dari akibat yang ditimbulkannya dapat merugikan orang lain, baik secara lahir maupun secara batin. Pelaku tindak pidana yang menyebarkan data pribadi dikategorikan sebagai Kesengajaan (Opzet) yang bersifat tujuan, sehingga patutlah tindakan penyebaran data pribadi dapat dikenakan ancaman hukuman sebagaimana diatur dalam UUD ITE maupun UU PDP. Penegakan hukumnya terhadap tindakan penyebaran data pribadi  sampai saat ini sangatlah minim serta sulit dilakukan, asas legalitas menjadi permasalahan dalam penegakan hukumnya, sehingga setelah disahkannya UU PDP menjadi angin segar bagi para penegak hukum yang karenanya penegakan hukum atas penyebaran data pribadi memiliki dasar hukum yang kuat.